Efektivitas Kunyit (Curcuma longa Linn) terhadap Esherichia coli dan Bacillus subtilis: Effectiveness of Turmeric (Curcuma longa Linn) against Esherichia coli and Bacillus subtilis - Rini, Chylen Setiyo; Rohmah, Jamilatur; Widyaningrum, Leni Yuroh (Medicra (Journal of Medical Laboratory Science/Technology), 2018)
Herbal plants that serve as a drug, one of which is turmeric that has a role as an antioxidant, antimicrobial, anti-cancer, digestive disorders. Because it contains compounds curcumin and essential oils. The purpose of this research is to know the optimal concentration of dry extract of turmeric rhizome (Curcuma longa L) in inhibiting the growth of E. coli and Bacillus subtilis. This research method using diffusion agar Kirby Bauer. In this study, turmeric extract at 15% concentration had antibacterial efficacy against Bacillus subtilis (0,7 mm) greater than Escherichia coli (0,63 mm).